Hubungan Dimensi dan Tipe Partisipasi Petani Cabai pada Kegiatan Fungsi Pemasaran di Titik Kumpul Pakem Kabupaten Sleman Indonesia: Relationship between Dimensions and Types of Chili Farmer Participation in Marketing Function Activities at Pakem Gathering Point, Sleman Regency, Indonesia - Qurayma, Vinka Anandani; Budiarto, Budiarto (Journal of Agricultural Social and Business, 2025)
This study aims to examine the dimensions and types of chili farmers' participation in marketing function activities at the Pakem Gathering Point, Sleman Regency, Indonesia. This study uses a qualitative approach with a case study research type. The selection of informants in this study was carried out purposively and snowball. The informants in this study were the Head of the Sleman Regency Chili Auction Market, Chili Farmers at the Pakem Gathering Point, the Management of the PPHPM Cooperative, Sleman Regency, and the Supervisor of the Sleman Regency Chili Auction Market. The data sources used were primary data and secondary data. Data collection techniques used observation, interviews, and documentation with data validity testing using source triangulation. Data analysis techniques included collecting data, reducing data, presenting data and drawing conclusions and verification. The results of the study showed the participation of chili farmers in implementing marketing functions at the Pakem Gathering Point. Marketing functions consist of exchange functions, physical functions, and facilities provision functions. In this study, chili farmers at the Pakem Gathering Point were involved in every dimension of participation starting from the planning, implementation, utilization of results, and monitoring and evaluation dimensions. Chili farmers are also involved in passive/manipulative participation types, to provide information, consultation, for material incentives, interactive, and self-mobilization.